Strengthening Economic Literacy to Minimize Consumptive Online Shopping Behavior among Generation Z in West Lombok Regency - Fathurrahman; Muhammad Habibullah Aminy; Baiq Santi Rengganis; Mardiyanto Rahayu, Slamet (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The growth and development of technology in everyday life has the potential to improve people's welfare. The level of public understanding of economic literacy is very important because it plays a role in economic management. The knowledge level of economic literacy in generation Z still needs strengthening. Therefore, community service activities were carried out in the form of strengthening economic literacy to minimize consumptive online shopping behavior among generation Z in Kekait Village, Gunungsari District, West Lombok Regency. Based on the community service activities that have been carried out, it can be seen that partners have given positive responses, including: acquiring new knowledge regarding economic literacy and digital financial platforms; the community wants to immediately implement good economic planning and management and intend to have digital savings. Sustainability of this activity is needed as a form of monitoring and evaluation of assistance in an effort to provide solutions to problems faced by partners.